Best methods for the analysis of change: recent advances, unanswered questions, future directions - Collins, Linda M.; Horn, John L. (American Psychological Association, 1991)
Analysis of longitudinal data using latent variable models with varying parameters -- Source of bias in longitudinal investigations of change -- Ordinal methods in the assessment of change -- Models for learning data -- Application of time series methods to moderate span longitudinal data -- Interindividual differences in intraindividual change -- Issues in factorial invariance -- Prediction of growth -- Measurement in longitudinal research -- Latent variable models for studying differences and change -- Assessing familial and nonfamilial sources of parent-child attitude resemblance over two measurement occasions -- Implications of a multidimensional latent trait model for measuring change -- Qualitative transitions amid quantitative development -- Behavior genetic studies of change -- Interpreting and estimating indirect effects assuming time lags really matter -- Longitudinal studies of disease and cognitive function -- Modeling incomplete longitudinal and cross-sectional data using latent growth structural models -- How long did it take? : using survival analysis in educational and psychological research